THE IMPORTANCE OF TEACHING ENGLISH VIA COMMUNICATIVE METHODS IN DIFFERENT LEVELS (Educator Insights: Journal of Teaching Theory and Practice, 2025)
English language is deemed as global language and the importance of teaching communication is real issue today. In this article, the importance of communicative skills is analyzed and suggested some methods of developing communicative skills in elementary, intermediate and advanced learners.